Post-exercise taurine administration enhances glycogen repletion in tibialis anterior muscle - Yumiko Takahashi; Yutaka Matsunaga; Yuki Tamura; Eiki Urushibata; Shin Terada; Hideo Hatta (Japanese Society of Physical Fitness and Sports Medicine, 2014)
Previous studies suggested that taurine (2-aminoethanesulfonic acid) administration enhances glucose uptake, one of the rate-limiting factors for glycogen synthesis. In this study, we investigated the effects of post-exercise taurine administration on glycogen repletion in skeletal muscle in ICR mice. In experiment 1, we orally administered either taurine (0.5 mg/g body weight) solution or physiological saline immediately after treadmill running at 25 m/min for 90 min. The serum free fatty acid (FFA) concentration at 60 min after the exercise was significantly higher in the taurine-treated group compared with the control group (p < 0.05). At 120 min after the exercise, the tibialis anterior muscle glycogen concentration in the taurine-treated group was significantly higher than that in the control group (p < 0.05). In experiment 2, we orally administered either glucose (1 mg/g body weight) solution or glucose solution containing taurine immediately after and at 60 min after the exercise. The area under the curve (AUC) for blood glucose concentration from 0 to 60 min after the exercise was significantly smaller in the taurine-treated group compared with the control group (p < 0.01). Our results show that post-exercise taurine administration enhances glycogen repletion in skeletal muscle. Higher skeletal muscle glycogen concentration by taurine administration may be partly due to the acceleration of glucose uptake. In addition, as the elevation of blood FFA level leads to an increase in fat oxidation, it is possible that a higher serum FFA concentration by taurine treatment is related to the sparing of carbohydrate for glycogen repletion.